A permanent magnet motor. - Misron, Norhisam; Ng, Seng Shin; Rizuan, Suhairi; Raja Othman, Raja Nor Firdaus Kashfi; Jelani, Abdul Razak (2011)
The present invention is about slit feature 145 and arrangement of permanent magnet 142 for cogging reduction of permanent magnet motor 100. The slit feature 145 can reduce the cogging torque that usually faces by single phase permanent magnet motor 100. Basically, the introduction of this slit features 145 can be applied to various operation of permanent magnet motor 100 which includes brushless permanent magnet DC motor (BLDC), interior permanent magnet motor (IPM) and synchronous permanent magnet motor (SPM). The cogging reduction is required to provide smoother self-starting torque. The permanent magnet motor 100 consist of two mains part know as stator 120 and rotor 140. The stator 120 consists of number of coils 122 where as rotor 140 consists of permanent magnets 142 and slit features 145. The application of the product related to power tools which covers all aspect of fields.